Decolonising Indigenous-state democratic dialogue. An analysis of the Sámi consultation process on the Norwegian Education Act - Slaviero, Anna (UiT Norges arktiske universitet, 2024)
This thesis examines the consultation process between the Sámediggi and the Norwegian government regarding the Education Act approved in 2023, adopting the Sámediggi’s perspective. Consultations are a central mechanism in international law for Indigenous peoples to influence decision-making processes and outcomes on matters that may affect their interests and cultures. However, there is a gap between the legal standards and actual implementation: often, consultations are reduced to a bureaucratic requirement and foster unequal relationships of colonial nature. Previous experiences show that, despite its reputation for advanced protection of Indigenous rights, Norway does not always implement in all respects its obligation to consult the Sámi people. The Education Act’s main case documents and interviews with consultation participants describe what led the Sámediggi to withdraw its consent: the disagreement with the legislative proposal because it does not sufficiently strengthen Sámi pupils’ rights, and the discontent with how Norwegian authorities carried out the process. This research indicates a divergence between the government’s preparatory work on the Sámi Act’s consultation provisions and its actions in the Education Act case. This confirms that the implementation of consultations is still not based on shared understandings and substantiates the need for guidelines to integrate the procedure within the authorities’ work. Furthermore, this research applies the essential elements of the epistemic and ethical functions of deliberative democracy to the case, revealing a lack of epistemic trust and reciprocity that significantly limits the Sámediggi’s influence. Thus, the thesis calls for a decolonial practice-oriented approach to deliberative dialogues to reduce the epistemic and socio-political asymmetries between Indigenous peoples and state authorities. Deliberative democrats must acknowledge colonial logic intrinsic in deliberative theory and practice and reconstruct deliberative spaces based on the ...